San Jerónimo en la onomástica de la familia Martí de Torres- Aguilar y su proyección en el retablo cuatrocentista de San Martín, del Museo de Bellas Artes de Valencia. - RUBIO VELA, AGUSTÍN (Scripta, 2020)
We have studied the family onomastics of the Martí de Torres-Aguilar, who commissioned the 15th-century raredos St Martin, St Ursula and St Anthony Abbot, a prominent piece of the Valencian gothic. This study, and the iconographic analysis of its main panels, beg the question whether the represented saint can actually be St Anthony Abbot. Both the onomastics and the iconographic tradition suggest that this figure should be matched to St Jerome.